In other Los Angeleses : multicentric performance art - Cheng, Meiling, 1960- (University of California Press, 2002)
Performance art and Los Angeles, two subjects spectacularly resistant to definitions, illuminate each other in this searching study by Meiling Cheng. A marginal artistic pursuit by choice as well as necessity, performance art has flourished in and about "multicentric" Los Angeles for nearly four decades, finding its own centers of activity, moving and changing as the margins have reconstituted themselves.